1991
DOI: 10.1080/03014469100001552
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and environmental factors affecting fetal growth in Papua New Guinea

Abstract: We studied 738 live singleton births in Papua New Guinea to examine the contribution of ethnic origin and environmental factors to birth weight and gestation. Maternal history, examination and post-partum anthropometry, infant anthropometry and clinical gestational assessment were performed, and placental blood slides and histology were examined. Mothers from Highlands provinces who delivered on the coast had larger babies (mean birthweight 3.34 SD 0.48 kg) than either indigenous coastal mothers (mean 3.10 SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…Pregnant women in Madang have high spleen rates (50%) at first antenatal visit (Brabin, Brabin, Sapau and Alpers 1988), and monthly malaria incidence during pregnancy averages 20% in primigravidae and 15% in multigravidae (Brabin et al 1990b). This contrasts sharply with Goroka, where malaria in pregnancy is exceptional and splenomegaly unusual (Primhak and MacGregor 1991). The high prevalence of splenomegaly during pregnancy in Madang is associated with an increased risk of malaria-related anaemia, as many women have spleens which are several centimetres Ann Hum Biol Downloaded from informahealthcare.com by Michigan University on 11/03/14…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Pregnant women in Madang have high spleen rates (50%) at first antenatal visit (Brabin, Brabin, Sapau and Alpers 1988), and monthly malaria incidence during pregnancy averages 20% in primigravidae and 15% in multigravidae (Brabin et al 1990b). This contrasts sharply with Goroka, where malaria in pregnancy is exceptional and splenomegaly unusual (Primhak and MacGregor 1991). The high prevalence of splenomegaly during pregnancy in Madang is associated with an increased risk of malaria-related anaemia, as many women have spleens which are several centimetres Ann Hum Biol Downloaded from informahealthcare.com by Michigan University on 11/03/14…”
Section: Discussionmentioning
confidence: 90%
“…In the Highlands an earlier report for the previous decade showed a comparable birthweight distribution to this Goroka sample (Greenfield 1983). An earlier study suggested that migration was not thought to be an important factor influencing birthweight distribution in coastal and highland populations (Primhak and MacGregor 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where sample size is very low (<5-10), even significant differences are likely to be vulnerable to uncontrolled variables such as parity and maternal factors (cf. Allen 1989, Primhak andMacGregor 1991), and should be viewed very cautiously. Elsewhere it may be helpful to keep in consideration the absolute values of the results and not to attend solely to statistical significance.…”
Section: Resultsmentioning
confidence: 98%
“…Haas, Moreno-Black, Frongillo, Pabon, Pareja, Ybarnegaray and Hurtado 1982). Highland/lowland differences within PNG's more modest altitude range have also been reported, but here it is lowlanders who generally have the lower birthweights: the complex of causes identified includes ethnic origin and maternal nutritional status (Aitken 1987, Primhak andMacGregor 1991). The East Mianmin birthweights are within the expected range for a highlands population, albeit the lower part of it (cf.…”
Section: Group Differencesmentioning
confidence: 86%